A New Radiographic Measurement Method for Evaluation of Tibial Torsion: A Pilot Study in Adults - Güven, Melih; Akman, Budak; Ünay, Koray; Özturan, Engin Kutay; Çakıcı, Hüsamettin; Eren, Abdullah (Clinical orthopaedics and related research, 2009)
Computed tomography (CT) frequently is used to determine torsional abnormalities. However, its use in clinical practice may be limited. We present a new method for measuring tibial torsion using conventional radiographs. We compared the method with several clinical methods and with CT measurement in 44 lower extremities of 25 subjects. The radiographic method agreed well with all of the clinical methods, and this agreement was better than agreement between CT and clinical examination. The best agreement was between thigh-foot angle and the radiographic method. The proposed radiographic measurement is a practical method for evaluation of tibial torsion in outpatient clinics without the need for specialized equipment. Level of Evidence: Level II, diagnostic study. See the Guidelines for Authors for a complete description of levels of evidence.